2004
DOI: 10.1562/2004-07-20-ra-237
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced DNA Cleavage and Cellular Damage in Human Dermal Fibroblasts by 2,3-Diaminophenazine

Abstract: Aromatic amines, such as o-phenylenediamine (OPD), have been used extensively in commercial hair dyes and in the synthesis of agricultural pesticides. Air oxidation of OPD results in the formation of 2,3-diaminophenazine (DAP). Although the mutagenic toxicity of DAP has been shown in both prokaryotic and eukaryotic systems, its phototoxicity remains largely unexplored. This study focuses on the pH-dependent photophysical properties of DAP and demonstrates its ability to photoinduce DNA damage to pUC19 plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The experiments in the present study identified effects from single and multiple PAHs with the inclusion of UV exposure. Studies have also shown that other compounds such as pesticides and dyes can cause photo‐induced toxicity . The effect of phototoxicity for other aquatic contaminates besides PAHs identifies a potential for adverse effects in aquatic systems well below non‐UV exposure guidance.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments in the present study identified effects from single and multiple PAHs with the inclusion of UV exposure. Studies have also shown that other compounds such as pesticides and dyes can cause photo‐induced toxicity . The effect of phototoxicity for other aquatic contaminates besides PAHs identifies a potential for adverse effects in aquatic systems well below non‐UV exposure guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the dissolved O 2 was not limiting under the studied conditions. Since DAP is fluorescent [16], a fluorometric format for the assay could be explored.…”
Section: Introductionmentioning
confidence: 99%